Metal Organic Framework@Polysilsesequioxane Core/Shell-Structured Nanoplatform for Drug Delivery - Liangyu Lu; Mengyu Ma; Chengtao Gao; Hongwei Li; Long Li; Fuping Dong; Yuzhu Xiong (MDPI AG, 2020)
Modern pharmaceutics requires novel drug loading platforms with high drug loading capacity, controlled release, high stability, and good biocompacity. Metal−organic frameworks (MOFs) show promising applications in biomedicine owing to their extraordinarily high surface area, tunable pore size, and adjustable internal surface properties. However, MOFs have low stability due to weak coordinate bonding and limited biocompatibility, limiting their bioapplication. In this study, we fabricated MOFs/polysilsesquioxane (PSQ) nanocomposites and utilized them as drug carriers. Amine-functionalized MOF (UiO-66-NH2) nanoparticles were synthesized and encapsulated with epoxy-functionalized polysilsesquioxane layer on the surface via a facile process. MOFs possessed high surface area and regular micropores, and PSQs offered stability, inertness, and functionality. The obtained UiO-66-NH2@EPSQ nanocomposites were utilized as carriers for ibuprofen, a drug with carboxylic groups on the surface, and demonstrated high drug loading capacity and well-controlled release property. The UiO-66-NH2@EPSQ nanocomposite exhibited low cytotoxicity to HeLa cells within a wide concentration range of 10−100 µg/mL, as estimated by the MTT method. The UiO-66-NH2@EPSQ drug release system could be a potential platform in the field of controlled drug delivery.